Soybean performance at different sowing times and plant distribution - Carmo, Eduardo Lima do; Braz, Guilherme Braga Pereira; Simon, Gustavo André; Silva, Alessandro Guerra da; Rocha, Antônio Germano Carpim (Revista de Ciências Agroveterinárias, 2018)
Favorable periods to sowing as well as the spatial arrangement in which plants are found in the growing area are factors that directly influence soybean yield. The best equidistance between plants for a certain growing period may result in greater use of water, light and nutrients by plants. In this context, in two summer’s crops, two field trials were carried out in order to evaluate the agronomic performance of soybean grown at different sowing periods and spatial plant distribution. The experimental design was a randomized complete block design in subdivided plots with four replications. In the plots, four equidistant sowing periods of 15 days from October 3 (2014/15 and 2015/16) were allocated and in the subplots, we arranged, randomly, the traditional and narrow plant spacing (inter-row spacing of 0.5 m and 0.25 m, respectively). At harvest, morphological characteristics, yield components and grain yield were evaluated. The sowing time influenced the morphological characteristics and yield components of soybean. Delaying the sowing season provided lower grain yields. Soybean cultivars behave differently in relation to the reduction of sowing inter-row spacing. BMX Desafio RR® presented higher yield when cultivated in 0.25 m inter-row spacing compared to traditional spacing (0.5 m).